PENGARUH EVA, MVA DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES - Sri Rahayu, Ni Made Putri; Dana, I Made (E-Jurnal Manajemen, 2016)
The stock price is indicator of the success of the management of the company, if a company's stock price increases, the investor considers that peruasahaan succeed in managing its business, on the contrary, if the stock price has decreased continuously means may reduce the company's value in the eyes of investors. The purpose of this study was to determine the influence of EVA, MVA as well as the liquidity of the stock price on the manufacturing sub-sector of food and beverage listed on the Indonesia Stock Exchange in 2010-2014. Data collection methods used in this study is a non-participant observation method and using the technique of determining the saturation sampling ( census ) . Total population of this experiment is the entire manufacturing sub sekto food and beverages that are still active are listed in the Indonesia Stock Exchange 2010-2014 period with a total population of 13 companies . The data analysis technique used is the technique of multiple linear regression analysis . Based on the analysis found EVA significant negative effect on stock prices , MVA and liquidity in this study significant positive effect on stock prices.
Keywords: stock price, economic value added (EVA), market value added (MVA), liquidity